Innovative governance for the future: Will gender diversity on boards enhance business performance in the European insurance industry? - María Encina Morales de Vega; María-Carmen García-Centeno; Ricardo Palomo-Zurdo (European Research on Management and Business Economics, 2025)
Recently, advocacy for gender diversity in corporate governance has intensified, following the hypothesis that heterogeneous boards can optimize management processes and improve financial performance. Existing literature primarily focuses on the banking or financial industry, with limited research on European insurers. Using a sample of 22 insurers included in EUROSTOXX 600 index over 2013–2023, a dynamic panel data model is employed to assess the impact of the presence of women on board and chair positions on Return on Equity (ROE) and Return on Assets (ROA), effectively accounting for unobserved firm characteristics and time-varying data. The results reveal that a female CEO increases performance by 0.3 %, higher female board representation improves returns by 3 %, and a smaller pay gap increases performance by 1 %. On the contrary, the existence of a quota does not have a significant influence due to issues with its design and implementation. These findings support the need to increase the number of women on insurers’ boards to enhance performance and strengthen a company's ethical standing and social responsibility. They are consistent with the literature review, underscoring the significance of gender equality policies in management for enhancing efficiency and innovation in the insurers’ future.